Designing Typography: Theory & Inspirational Artworks / Nadia Sigi Prameswari, Roziani Mat Nashir@Mohd Nasir and Nurul Amira Ramli - Prameswari, Nadia Sigi; Mat Nashir@ Mohd Nasir, Roziani; Ramli, Nurul Amira (Department of Liberal Studies, College of Creative Arts, Universiti Teknologi MARA, Kelantan, 2024)
Many people ask, "Do you still need to learn typography in today's digital age?". Find the font according to what we like. Change the font size as you want. Adjusts kerning automatically. Change the font shape. Then what else cannot be done easily through smart devices? Typography has indeed undergone a shift due to civilization and technology. So, it seems that letters become something very trivial in daily life. Not everyone can understand the essence of typography. The sophistication of tools makes all can easily create typography artworks, but not all can think typographically. A rarity in the middle of today's easy world is the balance between thoughts and feelings. Many miss the feeling of digital speed and practicality until they forget to apply the essential typographic principles. It is a throwback when typography artworks produced with the sophistication of tools escape their functional value. This book's discussion invites the reader to take a more in-depth look at what typography is and why it should be typography. Appreciate a letter being part of a cultural product from a micro-typography and macro-typography point of view. Readers are invited to explore letters from various approaches by exploring ideas and research as the basis of exploration.